Improving Early Childhood Gross Motor Skills through Structured Rope-Jumping Activities - Pravista Indah Sari; Agung Rahmat (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the Study: This study aimed to investigate the effectiveness of structured rope-jumping activities in improving the gross motor skills of kindergarten children, particularly leg strength and body balance, through a Classroom Action Research approach implemented in two learning cycles. Methodology: This study employed Classroom Action Research using the Kemmis and Mc. Taggart spiral model consisting of planning, action, observation, and reflection stages. The participants were 14 kindergarten children aged 4–5 years. Data were collected using structured observation sheets assessing leg strength and postural balance during rope-jumping activities conducted across two intervention cycles and six learning sessions. Main Findings: The findings showed significant improvement in children’s gross motor skills after the implementation of rope-jumping activities. The percentage of children achieving good performance increased from 14.28% in the pre-action stage to 71.42% in Cycle I and 92.86% in Cycle II. Improvements were observed in children’s jumping ability, landing stability, movement coordination, confidence, enthusiasm, and participation during physical learning activities. Novelty/Originality of this Study: The novelty of this study lies in the integration of structured rope-jumping activities with progressive instructional modifications, including warm-up exercises, adjusted rope height, repeated practice opportunities, group-based activity organization, and reward reinforcement. This study provides a practical, low-cost, and developmentally appropriate gross motor intervention model that can be directly implemented in early childhood education settings.